A Proposal of the Management of the University Incubator of startups in Peru - Janqui Guzmán, Artemio (2020)
Business incubators in a university area are protected environments designed for the creation, implementation and startups develop of technology base, whose research results are generated for the university community, promote employment and economic increase, being every time more important in the countries and regions. Peru doesn’t have a model for an effective management. With this study proposes a management model. The analysis of the literature and the surveys on the context of innovation in the country, identify that the policy of entrepreneurial university, the management with highly qualified staff, the correct selection of startups, the adequate financing and the university-business-government link, are the fundamental axes of the management model of the university incubator in Peru, for achieve the startups success.